PENGEMBANGAN INSTRUMEN LITERASI NUMERASI KONTEKS SOSIAL BUDAYA DI SMK PLUS PAKUHAJI - Muhamad Yasin; Hepsi Nindiasari; Sukirwan Sukirwan (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to produce a Vocational Mathematics numeracy literacy instrument that has been tested for validity and reliability, as well as through a systematic analysis of the instrument using a test of discrimination and index of difficulty. This type of research is development research with the Wilson model and the Oriondo and Antonio models. Methods of data collection using interviews, expert validation sheets, questionnaires and numeracy literacy tests. Data were analyzed descriptively and quantitatively. The research results obtained were: 1) the expert's assessment stated that this numeracy literacy instrument was an appropriate instrument to use; 2) the readability test shows that this numeracy literacy instrument is in the "good" category, 3) the validity test shows that this instrument is valid; 4) this numeracy literacy instrument is a reliable instrument with a reliability value of ????????>????????????????????????; 5) has a good interpretation of discriminating power with conclusions that can be used without revision; 6) Average item difficulty index. So that the resulting instrument is a feasible instrument used to measure students' numeracy literacy